A nuclear matrix attachment site in the 4q35 locus has an enhancer-blocking activity in vivo: Implications for the facio-scapulo-humeral dystrophy - Petrov, Andrei; Allinne, Jeanne; Pirozhkova, Iryna; Laoudj, Dalila; Lipinski, Marc; Vassetzky, Yegor S. (Genome Research, 2008)
Facio-scapulo-humeral dystrophy (FSHD), a muscular hereditary disease with a prevalence of 1 in 20,000, is caused by a partial deletion of a subtelomeric repeat array on chromosome 4q. Earlier, we demonstrated the existence in the vicinity of the D4Z4 repeat of a nuclear matrix attachment site, FR-MAR, efficient in normal human myoblasts and nonmuscular human cells but much weaker in muscle cells from FSHD patients. We now report that the D4Z4 repeat contains an exceptionally strong transcriptional enhancer at its 5′-end. This enhancer up-regulates transcription from the promoter of the neighboring FRG1 gene. However, an enhancer blocking activity was found present in FR-MAR that in vitro could protect transcription from the enhancer activity of the D4Z4 array. In vivo, transcription from the FRG1 and FRG2 genes could be down- or up-regulated depending on whether or not FR-MAR is associated with the nuclear matrix. We propose a model for an etiological role of the delocalization of FR-MAR in the genesis of FSHD.